The Articulation of the Memorable: History and Inscription in Two Photographic Series by Res - Bertúa, Paula (Universidad de Chile. Facultad de Filosofía y Humanidades, 2017)
In the last two decades, Argentine photographer Res has registered through his camera itineraries, images and scenarios that invite a review of events and processes in the history of Latin America. The photographic series La ruta de Cortés (1999-2000) and necah 1879 (1996-2008) set up interesting visual devices for reading and recalling the past since they point, from the present and with a retrospective inclination, to traumatic and founding moments in Latin American history. Res’s work invites a reflection concerning the relationship between history and photography, focusing on the link that binds facts of the past with the way of thinking and the discursive and visual techniques of its recorded materials. What memory is carried by these magnetic spaces that the photographer walks and explores with his camera? How do his photographs interact with the stories plotted by historiography about the events to which he refers and with the iconographic tradition that precedes those images? The thesis that guides this work is that Res explores new ways of representing the past, refusing the reconstruction of facts and history as a linear and evolutionary series oriented towards a teleological destiny, suggesting instead a thought of the discontinuity that creates, from these intervals, figures of memory with aesthetic and political power.